일부지역 노인의 구강진료 이용행태와 관련요인 - 유미선; 천혜원; 주온주 (Han'guk Ch'iwisaeng Hakhoe chi, 2011)
Objectives : This study aimed at examining the aspects of utilization of the dental services in some regions and analyzing the related factors with a view to helping the old solve the dental problems and overcome the difficulties. Methods : This investigation was intended for 422 old people living in Jeon-ju city and Jang-su county from July 18, 2006 to August 25 by direct interviewing posing questions. The survey data sets were analyzed by chi-square,correlation, multiple regression and logistic regression. Results : 1. The average number of the existing teeth per an old person was 13.6 and the 28.8% of the old who didn’t use denture called for dentures. 2. The annual coefficient of utilization in dental services for an old person was 52.3% and the annual average visits to dental clinics were 3.12 days while 38.6% of the old experienced illegal dental treatments. 3. The affecting factors on the dental utilization for treatment were as follows: family income,dental clinics available, the number of existing teeth, the days of dental trouble, the recognition of the prevention of the dental disease, the knowledge for the dental treatment and the oral health judged by himself. 4. The major variables influencing the utilization of dental services were spouse presence, form of family, income, having a regular dental care, denture presence and the experience of inconvenience in living. Conclusions : To conclude, the following suggestions could be made. First, It was necessary that enforcement practice of free dental prosthesis service and application to the national health insurance in old people’s prosthetic therapy for government support because the economic factor was barrier to utilization of the dental services. Second, Dental clinic was required to the health center because availability of common dental services was big impact in utilization of the dental services. KCI Citation Count: 6